Re-evaluating soil moisture-based drought criteria for rainfed crops in peninsular India - Bal, Santanu Kumar; Shivaramu, Huchahanumegowdanapalya S.; Vijaya Kumar, Puppala; Lingaraj, Huggi; Sandeep, Vadakkemethel M.; Subba Rao, A. V. M.; Sarath Chandran, Malamal Alickal; Manikandan, Narayanan; Thimmegowda, Matadadoddi N.; Manjunatha, Melekote H.; Malleswari, Sadhineni N.; Tupe, Arvind; et al. (Frontiers in Environmental Science, 2024)
Peninsular India, being completely under the influence of monsoonal climate, suffers crop yield variability due to rainfall distribution-induced soil moisture constraints. Timely and appropriate assessment of this rainfall and soil moisture-induced crop yield variability serves as a key for exemplary relief assistance. Per cent available soil moisture (PASM) is one among several drought declaration indices followed by stakeholders in India for declaration of drought, needs re-evaluation as the existing criteria in unable to capture the yield loss due to ineffective classification of PASM categories. This study attempts to revise the agricultural drought classes by PASM based on relationships established between yield of major rainfed crops of the study region and PASM.Analysis of yield variability due to PASM was carried out based on long term observations in experiments conducted at five dry farming locations (Akola, Parbhani, Kovilpatti, Ananthapuramu and Bengaluru) of peninsular India. The average yield for each category of PASM was calculated and tabulated for regression analysis. The PASM versus yield in each group was correlated and regression equations were developed if significant positive correlations were established.The range of available soil moisture to obtain at least 50 percent of optimum yield in cereals (maize: 26 and finger millet: 52.9 PASM), pulses (pigeon pea: 37.2 PASM), oilseeds (soybean: 26.8 to 30.5, groundnut: 53.8 to 61.7 PASM) and commercial crops (cotton: 26.3 PASM) was 26 to 61 percent.The revised PASM-based drought classes (0-50 severe; 51-75 mild and 76-100 no drought) would help in drought declaration and precise identification of drought-hit areas for meaningful relief assistance.However, there is further investigation is needed to include a soil component for further fine-tuning of the criteria.